Simulation of the Effect of Keyhole Instability on Porosity during the Deep Penetration Laser Welding Process - Yue Kang; Yanqiu Zhao; Yue Li; Jianfeng Wang; Xiaohong Zhan (Metals, 2022)
The quality of a laser deep penetration welding joint is closely related to porosity. However, the keyhole stability seriously affects the formation of porosity during the laser welding process. In this paper, a three-dimensional laser welding model with gas/liquid interface evolution characteristics is constructed based on the hydrodynamic interaction between the keyhole and molten pool during the laser welding process. The established model is used to simulate the flow and heat transfer process of molten. The Volume of Fluid (VOF) method is used to study the formation and collapse of the keyhole and the formation of bubbles. It is found that bubbles are easy to form when the keyhole depth abruptly changes. There are three main forms of bubbles formed by keyhole instability. The front wall of the keyhole collapses backward to form a bubble. The back wall of the keyhole inclines forward to form a bubble. The lower part of the keyhole produces a necking-down effect, and the lower part of the keyhole is isolated separately to form a bubble. In addition, when the keyhole does not penetrate the base metal, the stability of the keyhole is high and the percentage of porosity is low.